Customers’ perception and experience in purchasing local fresh fruits from retail shops in Alor Gajah, Melaka / Syed Muhamad Anasrullah Said Hamzah - Said Hamzah, Syed Muhamad Anasrullah (Faculty of Plantation and Agrotechnology, 2018)
Limitations in setting up favorable retail market formats in terms of storage, presentation, arrangement of structure and the specified quality of the product is the main concern for retailers today (Tsiros & Heilman, 2005). Objectives of this study are to explore the key determinants of consumers choosing the favorable retail formats and to anticipate the trend of purchasing local fresh fruits. The method used for this study are by using primary data collected from survey using structured questionnaire and observation. Spearman correlation and descriptive statistics which are frequencies and cross tabulation are used for the first objective. Exploratory factor analysis and descriptive statistics which are frequencies and cross tabulation are used for the second objective. The result of factor analysis on factors that affect buyer choices when choosing local fruit sales store suggest that the buyer at this area have higher level of comfort and convenience in influencing the buyer choices when choosing local fruit sales store. Based on cross tabulation for close retail store and frequency visited for pineapple, it can be concluded that most frequent respondents making pineapple purchase at the closest retail store which is fruits stall in once a month. Based on cross tabulation for preferred retail store and gender for pineapple, it can be concluded that the most frequent respondents making pineapple purchase at the most preferred retail store which is fruits stall who are female. This study provides information to wholesaler, retailer and related government agency such as Federal Agricultural Marketing Authority (FAMA) to improve trend of purchasing local fresh fruits in the population of Alor Gajah, Melaka. Furthermore, it is to inform wholesaler, retailer and related government agency to emphasize the most key determinants of consumers choosing the favorable retail formats in Alor Gajah, Melaka.